Perception of feelings, blood glucose measurement and social distancing conditions in adults with type 1 diabetes mellitus during the COVID-19 pandemic in Brazil - Carneiro, Maria de Nazareth de Lima (2024)
Introduction: The recommended social distancing measures to prevent the spread of Covid-19 caused high mental suffering, mainly for those affected by diabetes mellitus due to multiple metabolic, inflammatory and vascular changes. Objective: This work aims to test the association between the perception of feelings, the measurement of blood glucose and the conditions of social distancing due to the Covid-19 pandemic in adults with type 1 diabetes in Brazil. Materials and methods: The research was approved by the Ethics Committee and Research with Human Beings, carried out through an online form, it is a cross-sectional, descriptive and analytical study, carried out during the month of July 2020. Results: 472 adults with DM1 participated, 50.4% said that social distancing was causing stress in their home environment. For statistical analysis, the Statistical Package for Social Sciences software, version 21, was used, a relationship was found between stress, hyperglycemia and less willingness to remain in social isolation; normoglycemia feeling of joy and greater willingness to remain in social isolation. Conclusion: Given this, it is observed that social distancing caused glycemic and mood changes in these individuals. Therefore, the inclusion of care in the health of this population should be considered, through different interventions with the multidisciplinary team.